2005
DOI: 10.1128/aem.71.11.6753-6761.2005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence Genes of Escherichia coli Isolates from Swine in Ontario

Abstract: A total of 318 Escherichia coli isolates obtained from diarrheic and healthy pigs in Ontario from 2001 to 2003were examined for their susceptibility to 19 antimicrobial agents. They were tested by PCR for the presence of resistance genes for tetracycline, streptomycin, sulfonamides, and apramycin and of 12 common virulence genes of porcine E. coli. Antimicrobial resistance frequency among E. coli isolates from swine in Ontario was moderate in comparison with other countries and was higher in isolates from pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
201
5
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(248 citation statements)
references
References 46 publications
39
201
5
3
Order By: Relevance
“…The present result showed that the resistance frequency of antimicrobials in porcine E. coli isolates in Japan is considered to be moderate compared with the results in several countries such as Denmark, the Netherlands, Spain, Sweden, Korea, Australia and the United States: resistance frequency of ampicillin (3.4-76.5%), oxytetracycline (10.3-99.2%) and trimethoprim (/sulfonamide) (7.5-59.1%) (3,4,8,10). As these results may reflect the differences in antimicrobial regimens in each country, a risk-management strategy for antimicrobial resistance in bacteria of animal-origin is necessary on the basis on the situation of antimicrobial-resistant bacteria in each country.…”
Section: Discussionmentioning
confidence: 81%
“…The present result showed that the resistance frequency of antimicrobials in porcine E. coli isolates in Japan is considered to be moderate compared with the results in several countries such as Denmark, the Netherlands, Spain, Sweden, Korea, Australia and the United States: resistance frequency of ampicillin (3.4-76.5%), oxytetracycline (10.3-99.2%) and trimethoprim (/sulfonamide) (7.5-59.1%) (3,4,8,10). As these results may reflect the differences in antimicrobial regimens in each country, a risk-management strategy for antimicrobial resistance in bacteria of animal-origin is necessary on the basis on the situation of antimicrobial-resistant bacteria in each country.…”
Section: Discussionmentioning
confidence: 81%
“…Associations of virulence factors with mobile genetic elements (MGEs) conferring drug resistance have been observed in E. coli [13,14] and enterococci [15], but in staphylococci, the connection of PSM-mec to SCCmec is rather unique [2]. PSM-mec can be found in diverse staphylococcal species, and these staphylococci originated from different host species.…”
Section: Ab5472361) and S Vitulinus (Ab5467801)mentioning
confidence: 99%
“…This can be attributed to the insertion of a 1865 bp long IS1182 element and between the primers, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 within mecI [11,12]. It was also negative in a S. vitulinus strain, which was mecR1-negative by array hybridisation.Associations of virulence factors with mobile genetic elements (MGEs) conferring drug resistance have been observed in E. coli [13,14] and enterococci [15], but in staphylococci, the connection of PSM-mec to SCCmec is rather unique [2]. PSM-mec can be found in diverse staphylococcal species, and these staphylococci originated from different host species.…”
mentioning
confidence: 99%
“…Genetic linkage of selected antibiotic resistance genes is common. For E. coli, respectively, association of tetA and sul1 is more frequently reported [9].…”
Section: Discussionmentioning
confidence: 99%
“…Among Gram-negative tet genes, the widespread tetA and tetB genes have been shown to be linked to other resistance genes. They are frequently associated with genes conferring resistance to streptomycin (strA, strB) and/or sulfamethoxazole (sul1, sul2) [9].…”
Section: Introductionmentioning
confidence: 99%